Outcomes Addressed by Whole-Body Electromyostimulation Trials in Sportspeople and Athletes—An Evidence Map Summarizing and Categorizing Current Findings - Reinhardt, Svenja; Berger, Joshua; Kohl, Matthias; von Stengel, Simon; Uder, Michael; Kemmler, Wolfgang (Sports, 2025)
Whole-body electromyostimulation (WB-EMS) is a time-efficient, joint-friendly, and highly customizable training technology that particularly attracts sportspeople and athletes looking to enhance performance, accelerate regeneration, and prevent injuries with WB-EMS. Based on a systematic review of the literature, the present evidence map aimed to provide an overview of outcomes addressed by WB-EMS in exercising cohorts of different levels. In summary, the search identified 34 research projects with 39 studies and 43 publications that addressed 79 outcome categories (e.g., isometric strength) with more than 300 single outcomes (e.g., isometric strength of leg extensors). Thirty-one studies focused on performance-related outcomes, four studies addressed regeneration-related outcomes, and eight studies reported outcomes related to anthropometry. A further 14 studies reported health- and safety-related outcomes. Twenty-five of the 31 studies that reported performance parameters addressed strength, ten power, 18 jumping, ten sprinting, six agility, six endurance, five anaerobic power, and one each flexibility or balance, and five studies reported sport-specific performance outcomes (e.g., shot velocity). Apart from outcomes concerning injury prevention or sport-specific complaints, there are in particular evidence gaps relating to the acute effects of WB-EMS on regeneration, particularly with respect to muscle recovery. Semiprofessionals/professionals were rarely addressed, and if so, primarily cohorts from team sports were evaluated, while no study focused on elite strength, endurance, or precision sports athletes.
CRIS-Team Scopus Importer:2025-10-10
Keywords: athletes; electromyostimulation; performance; regeneration; safety; sportspeople; whole-body electrostimulation